﻿Changes of ultrastructural organization in periodontal complex components in experimental periodontitis and its correction with quercetin - Andrii Demkovych; Lesia Rubas; Vitalii Luchynskyi; Yuliia Luchynska; Halyna Stoikevych; Volodymyr Machogan (Pensoft Publishers, 2022)
The article presents the results of study the changes of ultrastructural organization in the periodontal complex under conditions of experimental bacterial-immune periodontitis development and treatment effect of flavonol quercetin. Experimental bacterial-immune periodontitis in experimental animals was caused by injection of complex mixture of microorganisms diluted with egg protein into periodontal tissue. The evaluation of the ultrastructural character changes in the gingival area of the periodontal complex was carried out on the basis of electron microscopic examination. In a result study on the 7th day of the experiment were observed changes that manifested disorders of the connective tissue and vessels structure. It were also marked increased diffusive leukocytic infiltration of the connective tissue of the mucosal gingival lamina propria. There was some improvement in respect of the electron microscopic structure of the microcirculatory vessels on the 14th and 30th days of the experiment. The performed studies of hemocapillaries submicroscopic organization of the animal's gums mucous membrane in conditions of application quercetin for experimental periodontitis has shown that flavonol improved structural organization considerably. The use of quercetin improves the organization of all ultrastructured components of the periodontal complex in experimental periodontitis.